The use of semi‐compliant versus non‐compliant balloon systems for predilatation during the implantation of self‐expandable transcatheter aortic valves: Data from the VIenna CardioThOracic Aortic Valve RegistrY (VICTORY). (6th May 2021) - Mach, Markus; Szalkiewicz, Philipp; Poschner, Thomas; Hasan, Waseem; Andreas, Martin; Winkler, Bernhard; Hasimbegovic, Ena; Steinkellner, Theresia; Strouhal, Andreas; Adlbrecht, Christopher; Delle‐Karth, Georg; Grabenwöger, Martin
Abstract: Background: This study aimed to evaluate the differences in outcome arising from the use of semi‐compliant (SCB) versus non‐compliant balloon (NCB) systems for predilatation during self‐expanding transcatheter aortic valve replacement (TAVR). Methods: 251 TAVR procedures with the implantation of self‐expanding valves after predilatation were analyzed. SCB systems were used in 166 and NCB systems in 85 patients. The primary endpoint was defined as device success, a composite endpoint comprising the absence of procedural mortality, correct valve positioning, adequate valve performance and the absence of more than a mild paravalvular leak. The secondary endpoints were chosen in accordance with the valve academic research consortium (VARC‐2) endpoint definitions. Results: No significant differences were observed with regard to procedural device success between the SCB‐ and NCB cohort (SCB: 142 [85.5%%] vs. NCB: 77 [90.6%]; P = .257). There was a notable difference between the rates of conversion to open surgery and the postdilatation rate, both of which were higher for the NCB group (SCB: 1 [0.6%] vs. NCB: 4 [5.1%]; P = .042; SCB: 30 [18.1%] vs. NCB: 34 [40%]; P < .001). In a multivariate logistic regression analysis, the use of semi‐compliant balloon systems for predilatation was associated with a lower risk for postdilatation (OR: 0.296; 95% CI: 0.149‐0.588) and conversion to open surgery (OR: 0.205; 95% CI: 0.085‐0.493; P = .001) but not for device success. Conclusion: While the balloon compliance did not affect the procedural mortality, device success or the rate of paravalvular leakage, the use of semi‐compliant balloons for predilatation during TAVR should be investigated in larger randomized trials in the light of the lower rates of postdilatation and conversion to open surgery compared to their non‐compliant counterparts.